Prevalence and Economic Losses Due to Infectious Bursal Disease in Broilers in Mirpur and Kotli Districts of Kashmir - Farooq, M.; Durrani, F.R.; Imran, N.; Durrani, Z.; Chand, N. (International Journal of Poultry Science, 2003)
A systematic investigation was performed on the outbreaks of Infectious Bursal Disease (IBD) using data compiled during the years 1997 and 1998 from 50 broiler farms in Mirpur and Kotli districts. Average mortality due to IBD was 15.31±1.04% with a coefficient of variation of 48.04%. Farms located at various places and vitamin supplementation had no effect on mortality caused by IBD. Season, floor space/broiler, age of the bird, immunization schedule, interval between two batches, presence of coccidiosis in a flock and hygienic status of the farm had a significant effect (p<0.01) on prevalence of IBD. Higher losses (p<0.05) were found due to IBD in winter (19.84±2.10%) than those tabulated in spring season (9.00±2.74%). Losses were found to be higher (p<0.05) in over crowded houses (20.34±3.93%; <0.09m2/broiler) than in under (12.56±2.53%; >0.09m2/broiler) or optimally utilized housing (13.04±1.06%; 0.09m2/broiler). Significantly higher (p<0.05) losses were found in broilers at the age above 32 days (17.66±1.51%) than in broilers at 19-23 days of age (12.42±1.97%). Prevalence of IBD was higher (p<0.05) in those flocks immunized only once in their production life (23.03±1.27%) than in those produced under a standard immunization schedule (7.61±4.89%). Losses due to IBD were also higher when the duration between two batches was one week (22.28±10.28%) than at four week duration between two batches (12.80±2.78%). Insignificant differences were assessed in losses due to IBD when inter flock interval was either 2 or 3 week periods. Significantly higher (p<0.05) losses were found due to IBD in flocks experiencing coccidiosis problem (17.90±1.20%) than those having no coccidiosis problem before the onset of IBD (12.73±1.85%). Losses were less in flocks maintained under good hygienic conditions (6.03±1.33%) than those under poor hygienic conditions (21.63±2.19%). Mean economic losses due to IBD per broiler flock of 1734.50±119.91 and a flock of 1000 birds were Rs. 7846.87±1169.81/ and Rs. 4523.99±447.56/, respectively. Economic losses/year for the aforementioned flocks was Rs. 31701.38±2345.36/- and Rs. 18276.96±2388.91/-, respectively. Optimal utilization of floor space/broiler, protection of birds from extreme climatic conditions, following recommended immunization schedule, maintenance of good hygienic conditions at the farm and a flock interval of at least more than one week are suggested as important factors for reducing losses due to IBD in broilers in Mirpur and Kotli districts of Kashmir.